Outcomes and factors associated with relapse of vaccine-induced liver injury after SARS CoV-2 immunization: A nationwide study - Barreira-Díaz, Ana; Riveiro-Barciela, Mar; Fernández-Bonilla, Eva María; Bernal, Vanesa; Castiella, Agustín; Casado-Martín, Marta; Delgado, Carolina; Londoño, María-Carlota; Díaz-González, Álvaro; Pérez-Medrano, Indhira; Conthe, Andrés; Sala, Margarita; et al. (Annals of hepatology, 2024)
Different patterns of liver injury have been reported in association with the SARS-CoV-2 vaccines. The aim of this study was to describe a nationwide cohort of patients with SARS CoV-2 vaccine-induced liver injury, focusing on treatment and the evolution after further booster administration. multicentre, retrospective-prospective study, including subjects who developed abnormal liver tests within 90 days after administration of SARS-CoV-2 vaccination. 47 cases were collected: 17 after prime dose and 30 after booster. Age was 57 years, 30 (63.8 %) were female, and 7 (14.9 %) had a history of prior autoimmune hepatitis (AIH). Most cases were non-severe, though 9 (19.1 %) developed acute liver injury or failure (ALF). Liver injury tended to be more severe in those presenting after a booster (p=0.084). Pattern of liver injury was hepatocellular (80.9 %), mixed (12.8 %) and 3 (6.4 %) cholestatic. Liver biopsy was performed on 33 patients; 29 showed findings of AIH. Forty-one (87.2 %) patients received immunosuppressants, mostly corticosteroids (35/41). One required liver transplantation and another died due to ALF. Immunosuppression was discontinued in 6/41 patients without later rebound. Twenty-five subjects received at least one booster and 7 (28.0 %) relapsed from the liver injury, but all were non-severe. Recurrence was less frequent among patients on immunosuppressants at booster administration (28.6 % vs. 88.9 %, p=0.007). SARS CoV-2 vaccine-induced liver injury is heterogeneous but mostly immune-mediated. Relapse of liver injury after re-exposure to vaccine is frequent (28.0 %) but mild. Immunosuppression at booster administration is associated with a lower risk of liver injury.